Dilaton-induced variations in Planck constant and speed of light: An alternative to dark energy - Hoang Ky Nguyen (Physics Letters B)
We reveal a novel aspect of scale-invariant actions that allow matter to couple with a dilaton field: The dynamics of the dilaton can induce variations in the Planck constant ħ and speed of light c. Our mechanism for generating variable ħ and c in curved spacetimes via the dilaton offers a viable alternative account for late-time cosmic acceleration, bypassing the need for dark energy.